Mucopolysaccharide polysulfate promotes microvascular stabilization and barrier integrity of dermal microvascular endothelial cells via activation of the angiopoietin-1/Tie2 pathway. Issue 1 (July 2021) - Fujiwara-Sumiyoshi, Shiori; Ueda, Yuhki; Fujikawa, Mika; Osaki, Miho; Yamanaka, Naoki; Matsumoto, Tatsumi
Highlights: MPS increased the production of Ang-1 by HPC and the production of PDGF-BB by HDMEC. MPS directly activates the Ang-1/Tie2 signaling pathway by increasing the expression and phosphorylation of Tie2 in HDMEC. MPS enhanced the vascular barrier function in HDMEC by increasing the expression of claudin-5. The intradermal injection of MPS prevented VEGF-induced increase in vascular permeability in mouse skin. Abstract: Background: Mucopolysaccharide polysulfate (MPS) is a heparinoid and MPS-containing formulations are widely used as moisturizers for dry skin and to treat peripheral vascular insufficiency. Although MPS has therapeutic effects in skin diseases with microvascular abnormalities, the effects of MPS on microvascular function remain incompletely understood. Objective: The aim of this study was to evaluate the functional activities of MPS on human pericytes (HPC) and human dermal microvascular endothelial cells (HDMEC) in vitro, and on microvascular permeability of the skin. Methods: The protein expression of angiopoietin (Ang)-1 in HPC, and platelet-derived growth factor-BB (PDGF-BB) and phosphorylated tyrosine-protein kinase receptor 2 (Tie2) in HDMEC were measured in the presence or absence of MPS. The vascular barrier was evaluated by the expressions of claudin-5 and vascular endothelial (VE)-cadherin, and transendothelial electrical resistance (TEER). Results: In HPC, MPS dose-dependently enhanced Ang-1 secretion, which activated Tie2 in HDMEC. In HDMEC, MPS significantly increased the production of PDGF-BB, which is important for the recruitment of HPC to the vascular endothelium, and significantly increased the phosphorylation of Tie2, which results in the activation of the Ang-1/Tie2 signaling . MPS significantly increased the expression of tight junction protein claudin-5 and TEER in the HDMEC. Moreover, the intradermal injection of MPS prevented vascular endothelial growth factor-induced increase in vascular permeability in mouse skin. Conclusion: We found that MPS promoted microvascular stabilization and barrier integrity in HDMEC via Ang-1/Tie2 activation. These results suggest that MPS might improve microvascular abnormalities in various diseases accompanied by disturbances in Ang-1/Tie2 signaling.